High expression of CD26 accurately identifies human bacteria‐reactive MR1‐restricted MAIT cells. Issue 3 (29th March 2015) - Sharma, Prabhat K.; Wong, Emily B.; Napier, Ruth J.; Bishai, William R.; Ndung'u, Thumbi; Kasprowicz, Victoria O.; Lewinsohn, Deborah A.; Lewinsohn, David M.; Gold, Marielle C.
Summary Mucosa‐associated invariant T (MAIT) cells express the semi‐invariant T‐cell receptor TRAV1–2 and detect a range of bacteria and fungi through the MHC‐like molecule MR1. However, knowledge of the function and phenotype of bacteria‐reactive MR1‐restricted TRAV1–2+ MAIT cells from human blood is limited. We broadly characterized the function of MR1‐restricted MAIT cells in response to bacteria‐infected targets and defined a phenotypic panel to identify these cells in the circulation. We demonstrated that bacteria‐reactive MR1‐restricted T cells shared effector functions of cytolytic effector CD8+ T cells. By analysing an extensive panel of phenotypic markers, we determined that CD26 and CD161 were most strongly associated with these T cells. Using FACS to sort phenotypically defined CD8+ subsets we demonstrated that high expression of CD26 on CD8+ TRAV1–2+ cells identified with high specificity and sensitivity, bacteria‐reactive MR1‐restricted T cells from human blood. CD161hi was also specific for but lacked sensitivity in identifying all bacteria‐reactive MR1‐restricted T cells, some of which were CD161dim. Using cell surface expression of CD8, TRAV1–2, and CD26hi in the absence of stimulation we confirm that bacteria‐reactive T cells are lacking in the blood of individuals with active tuberculosis and are restored in the blood of individuals undergoing treatment for tuberculosis.